The COVID-19 Health Crisis And Its Framing: Approaches Used by the Print Media for Coverage - Odoemelam, Chika Ebere (Advances in Social Sciences Research Journal, 2021)
Almost all the countries of the world have witnessed the outbreak of a global health pandemic known as COVID-19 like never before. This pandemic has negatively impacted the economic, health, social, and overall well-being of humanity. The framing analysis approach allows scholars to explore the media’s roles in developing health, economic, political, social, and cultural issues facing society daily. Besides, framing entails an interplay between leading social values and the efforts to tinker with them. This study explored what aspects of framing approaches the major newspapers have created for their readership in Nigeria in understanding the COVID-19 health pandemic that has rattled the entire world since January 2020. The research findings revealed that the six selected newspapers amplified coverage of the pandemic using the frames of economic issues, public healthcare crisis, health workers strike, and corruption with different ferocity and salience. It was also found that the dominant news frames approaches of economic issues, corruption, and public healthcare crisis received negative tone coverage across all the sampled papers at varying degrees. The tone approaches used in framing the COVID-19 pandemic in the selected newspapers were positive, negative, and neutral tones, which are possibly rooted in their editorial policies and political beliefs.